OPTIMATION PARAMETERS OF CNC MILLING PROGRAMMING MACHINE ON THE PROCESS TIME AND ITS EFFECT ON THE EFFICIENCY - Lydia Anggraini; Ivan Junixsen (President University, 2018)
The problems revealed in this research is about Optimization parameters of CNC milling programing machine on the process time and its effect on the efficiency. The purpose of this research are to know the effect of feed rate, depth of cut, and maximum stepdown on processing time in CNC milling programming and searching for the best machining parameters that yield optimal processing time on CNC milling programming. The result can be in the simulation of machining distance or operation time, length of feed step or feed cut length, and length of step without feeding or fast traverse length. Experiment result data is used for see the influence, and contribution of each parameter to the machining process time, also the contribution of the optimized parameters for each process that makes the CNC milling machining process time, and cost will be more efficient.